Thermodynamic Modeling of Hydrogen Fuel Reformers Through Gibbs Energy Minimization - Coban, Mustafa Turhan; Genceli, Hadi; Asker, Mustafa; Turgut, Oguz Emrah; Turgut, Mert Sinan (WILEY-V C H VERLAG GMBH, 2026)
In this study, a framework for a hydrogen reformer is developed. The equilibrium compositions are predicted by using Gibbs free-energy minimization. In this context, six separate scenarios are developed for various reformer models in order to investigate the influence of different design parameters on hydrogen production and reformer performance. It is found that, for diesel, adiabatic steam reforming yields outlet temperatures ranging from 973 to 1273 K at pressures between 500 and 1500 kPa, with the highest hydrogen yield achieved at a steam-to-carbon ratio of 3.5. Isothermal steam reformers can achieve hydrogen production levels of 70%-80% at temperatures exceeding 1000 K. In the process of partial oxidation, temperatures exceeding 1200 K lead to a notable shift in gas composition, reducing CO from approximately 81% to 68% and increasing CH4 from around 18% to 32% as the O/C ratio and pressure increase. In contrast, autothermal reformers (ATRs) provide compositions that remain independent of pressure. As the framework is equilibrium-based, the reported compositions and parametric sensitivities represent thermodynamic upper-bound trends rather than predictive behavior.
Keywords: Gibbs free energy; hydrogen; optimization; reformer; thermodynamic modeling; CELL; DIESEL; PERFORMANCE; Electrochemistry; Energy & Fuels